2021
DOI: 10.1007/s11065-021-09519-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mindfulness-based Programs on Cognitive Function in Adults: A Systematic Review and Meta-analysis

Abstract: Mindfulness-based programs (MBPs) are increasingly utilized to improve mental health. Interest in the putative effects of MBPs on cognitive function is also growing. This is the first meta-analysis of objective cognitive outcomes across multiple domains from randomized MBP studies of adults. Seven databases were systematically searched to January 2020. Fifty-six unique studies (n = 2,931) were included, of which 45 (n = 2,238) were synthesized using robust variance estimation meta-analysis. Meta-regression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 143 publications
(134 reference statements)
2
58
1
1
Order By: Relevance
“…Furthermore, these studies used behavioral measures, both self and other (participant’s parents or teachers) informant ratings to assess treatment effects of MBIs on ADHD symptomology, whereas we used a computerized attention test. Usually, the effect sizes for neurocognitive variables in comparable trials are typically small, even more so if an active control group is used [ 27 ]. Since the trial was powered to detect changes in ADHD symptoms as assessed by behavioral measures, we were likely underpowered for neurocognitive variables, such as CPTs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies used behavioral measures, both self and other (participant’s parents or teachers) informant ratings to assess treatment effects of MBIs on ADHD symptomology, whereas we used a computerized attention test. Usually, the effect sizes for neurocognitive variables in comparable trials are typically small, even more so if an active control group is used [ 27 ]. Since the trial was powered to detect changes in ADHD symptoms as assessed by behavioral measures, we were likely underpowered for neurocognitive variables, such as CPTs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have potentially important implications for interventions to reduce anxiety and depression in adults with HD. First, there is support for the efficacy of interventions (e.g., mindfulness, cognitive training) to enhance specific aspects of executive functioning in typical populations (Whitfield et al, 2021) and those with other neurogenerative diseases (e.g., Multiple Sclerosis and Parkinson’s disease; Ghielen et al, 2019; Manglani et al, 2020). Second, there is ample evidence to support the efficacy of cognitive behavioral interventions to enhance skills that comprise secondary control coping skills, including acceptance and cognitive reappraisal, in the treatment and prevention of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Improving cognition is an important step toward dementia prevention, and future research is needed to delineate the mechanisms of action of these interventions and to utilize clinical endpoints (i.e., progression to mild cognitive impairment or dementia). [14,20]. While these evidence syntheses were not SCDspecific, SCD overlaps with both healthy cognitive aging (both lack objective cognitive impairment) and also MCI (both are associated with increased dementia risk).…”
Section: Introductionmentioning
confidence: 94%
“…Two recent reviews concluded that MBIs reduce depressive symptoms in older adults, although the evidence for anxiety was mixed [12,13]. Furthermore, a recent meta-analysis found that MBIs outperformed comparators for objective cognitive function outcomes in older (but not younger) individuals [14]. Health self-management programs (HSMPs) are a commonly used active comparator in MBI RCTs [15][16][17], although in other studies, they are the primary focus.…”
Section: Introductionmentioning
confidence: 99%